2018
DOI: 10.1177/1071100718798851
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Outcomes of Transfibular Total Ankle Arthroplasty

Abstract: Level IV, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…As reported by Valderrabano et al, short-term follow-up outcomes have highlighted an improvement in the AOFAS score from a mean value of 42.12 to 96.02, confirming our clinical findings. Regarding a totally different TAR approach, Mosca et al (2021) and Usuelli et al (2019) showed how the AOFAS score improved from an average preoperative mean value of 33.8 to a post-operative mean value of 88.5 [ 13 , 14 , 15 ]. Our findings and our clinical results appear comparable, even superior, compared to other similar and recent studies in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Valderrabano et al, short-term follow-up outcomes have highlighted an improvement in the AOFAS score from a mean value of 42.12 to 96.02, confirming our clinical findings. Regarding a totally different TAR approach, Mosca et al (2021) and Usuelli et al (2019) showed how the AOFAS score improved from an average preoperative mean value of 33.8 to a post-operative mean value of 88.5 [ 13 , 14 , 15 ]. Our findings and our clinical results appear comparable, even superior, compared to other similar and recent studies in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, Usuelli et al reported a 98.9 % survival rate at 24 months with a rate of major complications requiring surgery of 11.2 %. We found in our patients a survival rate of 100% with a decrease in VAS from 7.81 pre-operatively to 2.29 post-operatively and major complications rate of 23.3 % [19].…”
Section: Discussionmentioning
confidence: 99%
“…The radiographic evaluation included weight-bearing anteroposterior (AP) and lateral views at baseline and after 3, 6, and every 12 months after the surgery. The angular measurements were made as described by Usuelli et al 30 Postoperatively, the talar and tibial components were viewed for subsidence, which was defined as a change in vertical position of prosthesis component ≥5 mm 2 . Radiolucency around tibial and talar components seen on AP and lateral radiographs was recorded ( Figure 1).…”
Section: Outcome Measuresmentioning
confidence: 99%